2015
DOI: 10.7124/bc.0008cb
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of chromosomal abnormalities and genes of the major histocompatibility complex to early pregnancy losses

Abstract: Aim. The determination of chromosomal abnormalities in samples from early pregnancy losses and allelic polymorphism of HLA-DRB1 and DQA1 genes in couples with recurrent miscarriage. Methods. Banding cytogenetic and interphase mFISH analysis, DNA extraction by salting method, PCR, agarose gel electrophoresis. Results. Cytogenetic and molecular-cytogenetic investigations of SA material identifi ed karyotype anomalies in 32.4 % of cases with prevalence of autosomal trisomy -42.65 %, triploidy -30.38 % and monosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The results obtained by Tkach et al ( 28 ) during genotyping of Ukrainian women with RM (HLA DQB1 0301 and DQA1 0501) were similar to Kazakh population. Iskhakov et al ( 29 ) showed a significant contribution of HLA DRB1 gene 15 allele to the increased risk of RM development.…”
Section: Discussionsupporting
confidence: 54%
“…The results obtained by Tkach et al ( 28 ) during genotyping of Ukrainian women with RM (HLA DQB1 0301 and DQA1 0501) were similar to Kazakh population. Iskhakov et al ( 29 ) showed a significant contribution of HLA DRB1 gene 15 allele to the increased risk of RM development.…”
Section: Discussionsupporting
confidence: 54%
“…The complexity of the immunological relationship between mother and fetus during pregnancy dictates the need to continue research, study additional SNP genes of the immune response. The results obtained by I. Tkach [ 38 ] during genotyping of Ukrainian women with RM – HLA DQB1*0301 and DQA1*0501 are similar to risk alleles for the Kazakh population. A. Iskhakov [ 39 ] showed a significant HLA DRB1 gene 15* allele contribution to the increased risk of RM development.…”
Section: Discussionmentioning
confidence: 72%